ZIBMAP: produk kesejahteraan kesihatan pelancong (ZIBMAP: product for tourists’ wellness) / Hassnah Wee, Nur Nadirah Abdul Wahab and Zamhariyah Ahmad Fudil - Wee, Hassnah; Abdul Wahab, Nur Nadirah; Ahmad Fudil, Zamhariyah (Universiti Teknologi MARA, 2020)
Tourists visiting destination in warm climate countries such as Malaysia might easily be affected with dehydration problem. Places like the Zoo requires tourist to walk intensively inside the Zoo area may cause dehydration if they do not consume enough plain water. This ZIBMAP innovative product intends to benefit the tourist wellness who visits the National Zoo, comes with an informative map and attractive infographic habitat, which can be kept as a souvenir. This innovative product is designed based on environmental friendly features that support the implementation of environmental sustainability. A feasibility survey on dehydration risk awareness and the potential of the product acceptance for commercialization was carried out using a quantitative method. A convenience sampling technique was used to identify 300 tourists visiting the National Zoo as respondents for this survey. Descriptive analysis results indicated that majority of respondents aware of the dehydration risk and supported the used of the ZIBMAP innovative product. The outcome of the study highlighted the potential of this product to be commercialized and contribute to tourists’ wellness.